Human Resource Management Practices of Egyptian Small and Medium Sized Enterprises: an Exploratory Investigation - Hani Shash, Ahmed (2011)
Small and medium sized enterprises (SME) are seen to have a great importance in a number of nations due to their important role in economic growth. Given their significance, SMEs have attracted a great number of management researchers, economists, and social scientists. A great number of academic studies have been trying to explore the SME management aspects; in particular, the practices adopted for human resource management (HRM). This paper investigates the determinants behind the HRM decision taken by the SME owners and managers in the Egyptian context and how this influences affect the prioritization of certain HRM key function over another. The findings of this study indicated that there exist several newly unexplored factors that influence the HRM decisions in Egyptian SMEs. Additionally, there seem to be a strong relation between the determinants and the level of importance of each HRM function perceived by the SME owner. Finally, the paper demonstrates how these findings have an impact on the field of Human Resource Management studies.